2018
DOI: 10.14739/2310-1210.2018.3.132127
|View full text |Cite
|
Sign up to set email alerts
|

Predicion of the functional outcome of cerebral ischemic supratentorial stroke acute period on the basis of spectral analysis of the brain bioelectrical activity

Abstract: The purpose of this study was to determine the most informative parameters of the brain bioelectrical activity spectral analysis for the functional outcome of cerebral ischemic supratentorial stroke (CISS) acute period prediction.Materials and methods. Prospective, cohort and comparative study was conducted among 103 patients in CISS acute period (61 men and 42 women, mean age was 67.7 ± 0.8 years). Electroencephalographic study was conducted on the 2 nd -3 rd day of the disease with the use of 19-channel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“…One study found no association between EEG-recorded seizures and GOS [37]. Another eight found associations between spectral power (alpha, theta and delta) and/or spectral power ratios and poor outcome, including: more delta activity [40,[45][46][47], less alpha activity [40,[45][46][47], greater theta activity [40,[46][47][48] but also less theta activity [45], greater DTABR [14,45] and higher Brain Symmetry Index score (denoting greater asymmetry) [49]. One study stated that qEEG frequencies predicted outcome but did not provide further detail [50].…”
Section: B) Identi Cation Of Ischaemic Versus Haemorrhagic Strokementioning
confidence: 99%
“…One study found no association between EEG-recorded seizures and GOS [37]. Another eight found associations between spectral power (alpha, theta and delta) and/or spectral power ratios and poor outcome, including: more delta activity [40,[45][46][47], less alpha activity [40,[45][46][47], greater theta activity [40,[46][47][48] but also less theta activity [45], greater DTABR [14,45] and higher Brain Symmetry Index score (denoting greater asymmetry) [49]. One study stated that qEEG frequencies predicted outcome but did not provide further detail [50].…”
Section: B) Identi Cation Of Ischaemic Versus Haemorrhagic Strokementioning
confidence: 99%
“…Перспективним є викорис тання електроенцефалографічного (ЕЕГ) дослідження для оцінювання функціонального стану церебральних структур [8]. У багатьох дослідженнях останніх років переконливо доведено високу діагностичну та прогностичну цінність спектрального аналізу біоелектричної активності головного мозку у пацієнтів з гострими ураженнями головного мозку ішемічного та травматичного ґенезів [9][10][11][12]. Дослідженню ЕЕГ-паттерну у пацієнтів з геморагічним півкульовим інсультом у зіставленні з виходом гострого періоду захворювання присвячені поодинокі роботи [13,14], що обґрунтовує актуальність досліджень, спрямованих на розробку електроенцефалографічних критеріїв прогнозування летального виходу гострого періоду ССВМК.…”
unclassified
“…Численними дослідженнями доведена діагностична та прогностична цінність електроенцефалографічного (ЕЕГ) дослідження в оцінці та моніторингу функціонального стану церебральних структур у пацієнтів з гострими ураженнями головного мозку різного ґенезу [5][6][7][8]. Так, досить висока чутливість ЕЕГ щодо детекції змін біоелектричної активності головного мозку, обумовлених гострою церебральною ішемією, дозволила розробити інформативні критерії прогнозування перебігу та виходу мозкового ішемічного інсульту [9]. Мілісекундна роздільна здатність, яка не доступна таким методам дослідження як позитронна емісійна томографія та функціональна магнітно-резонансна томографія, зробила можливим застосування ЕЕГ для здійснення моніторингу біоелектричної активності головного мозку підчас каротидної ендартеректомії з метою своєчасної верифікації ятрогенної церебральної ішемії [10].…”
unclassified
“…Зазначений контингент також відрізнявся більш глибоким рівнем неврологічного дефіциту, більшим обсягом осередку ураження та більш вираженим зсувом серединних структур мозку, що дозволяє розглядати наведені вище зміни ЕЕГ-патерну в якості нейрофізіологічних маркерів тяжкості ураження специфічних систем мозку супратенторіальної локалізації. Отримані дані узгоджуються з результатами інших досліджень, в яких було продемонстровано взаємозв'язок зсуву потужності спектру ЕЕГ-патерну убік повільнохвильової активності з тяжкістю ураження церебральних структур та виходом захворювання у пацієнтів з ішемічним інсультом [9,14] та гострими травматичними ураженнями головного мозку [8].…”
unclassified